Effects of alcohol and PARP inhibition on RNA ribosomal engagement in cortical excitatory neurons - Krishnan, Harish R.; Vallerini, Gian Paolo; Gavin, Hannah E.; Guizzetti, Marina; Rizavi, Hooriyah S.; Gavin, David P.; Sharma, Rajiv P. (Frontiers in Molecular Neuroscience, 2023)
We report on the effects of ethanol (EtOH) and Poly (ADP-ribose) polymerase (PARP) inhibition on RNA ribosomal engagement, as a proxy for protein translation, in prefrontal cortical (PFC) pyramidal neurons. We hypothesized that EtOH induces a shift in RNA ribosomal-engagement (RE) in PFC pyramidal neurons, and that many of these changes can be reversed using a PARP inhibitor. We utilized the translating ribosome affinity purification (TRAP) technique to isolate cell type-specific RNA. Transgenic mice with EGFP-tagged Rpl10a ribosomal protein expressed only in CaMKIIα-expressing pyramidal cells were administered EtOH or normal saline (CTL) i.p. twice a day, for four consecutive days. On the fourth day, a sub-group of mice that received EtOH in the previous three days received a combination of EtOH and the PARP inhibitor ABT-888 (EtOH + ABT-888). PFC tissue was processed to isolate both, CaMKIIα pyramidal cell-type specific ribosomal-engaged RNA (TRAP-RNA), as well as genomically expressed total-RNA from whole tissue, which were submitted for RNA-seq. We observed EtOH effects on RE transcripts in pyramidal cells and furthermore treatment with a PARP inhibitor “reversed” these effects. The PARP inhibitor ABT-888 reversed 82% of the EtOH-induced changes in RE (TRAP-RNA), and similarly 83% in the total-RNA transcripts. We identified Insulin Receptor Signaling as highly enriched in the ethanol-regulated and PARP-reverted RE pool and validated five participating genes from this pathway. To our knowledge, this is the first description of the effects of EtOH on excitatory neuron RE transcripts from total-RNA and provides insights into PARP-mediated regulation of EtOH effects.